Penerapan Model Challenge Based Learning dalam Pembelajaran Kewirausahaan Bahasa Sebagai Upaya Menghasilkan Wirausahawan Milenial - Anggraini, Purwati; Suyatno, Suyatno; Tjahjono, Tengsoe; Widodo, Joko (Universitas Hamzanwadi, 2024)
The Language and Literature Entrepreneurship course is oriented to two main aspects, namely value-oriented and goal-oriented. With the challenge based learning (CBL) learning model, this course is presented starting from the 2019/2020 academic year for semester VI students. At the time this research was conducted, this course was presented in three semesters, namely the even semester of 2019/2020, odd and even semester of the 2020/2021 academic year. This study aims to describe student responses related to the learning process and student experiences in Language and Literature Entrepreneurship courses. With qualitative descriptive research, this study consisted of 68 respondents who had taken courses. The results of this study were that respondents considered this course useful for the future, delivered with a challenging learning model, and inspiring learning materials. However, because this course was delivered during the pandemic, learning experienced several obstacles. This obstacle causes students to be less confident and some are not optimistic in entrepreneurship